Hepato-Protective Role of Vitamin C against Aspartame Induced Toxicity- An Experimental Rat Study. - Samia Siddiqui1, Naila Noor2, Hina Nazeer Khanzada3, Sajjad Ali Almani4, Imtiaz Ahmed5, Jahanzeb Khan6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Objective: To observe the hepato-protective effect of vitamin C supplementation through assessment of serum markers of liver function and histological alteration in liver caused by aspartame in Albino Wistar Rats Methods: Quasi-experimental study was carried out at Isra University, Hyderabad from March to August 2019. Thirty healthy adult male Albino Rats with body weight ranging from 250 to 300 grams were selected and were equally categorized in three groups as: Group A (received normal chow diet ad libitum), Group B (Aspartame l50mg/kg with normal diet) and Group C (Aspartame l50mg/kg and Vitamin C supplementation l00mg/kg with normal diet). After completion of experiment of 6 weeks, Biochemical (liver function tests) and histopathological analysis was performed in all groups. Statistical analysis of data was performed in SPSS version 24.Level of significance was set at p-value < 0.05. Results: Difference in mean pre- and post-experimental body weight was observed in all three groups. There was a statistically significant decline in the bodyweight, and an incline in relative liver weight of group B in comparison with groups A and C(p-value<0.05). Liver function markers were also significantly elevated in B in comparison with groups A and C(p-value<0.05).On histological examination Aspartame is significantly associated with lymphocytic infiltrative changes, fibrotic changes, necrotic changes, congested sinusoids and fatty changes ,p-values were quite significant. Additionally, consumption of vitamin C significantly prevented these changes (p-value/0.05). Conclusion: Ascorbic acid therapy is a potent hepato-protective regime showing promising results in aspartame induced hepatotoxicity.